Implementation of a School‐Based Educational Program to Increase Breast Cancer Awareness and Promote Intergenerational Transmission of Knowledge in a Rural Mexican Community. (26th June 2017) - Soto‐Perez‐de‐Celis, Enrique; Smith, David D.; Rojo‐Castillo, Maria Patricia; Hurria, Arti; Pavas‐Vivas, Alba Milena; Gitler‐Weingarten, Rina; Mohar, Alejandro; Chavarri‐Guerra, Yanin
Abstract: Background: Rural women have limited access to breast cancer education, which partially contributes to late diagnosis and treatment. In this pilot study, we tested the feasibility of implementing a school‐based breast cancer educational program for adolescents in a rural Mexican community. We hypothesized that the adolescents' knowledge on breast cancer would increase as a result of the program, and that there would be intergenerational transmission of that knowledge to their older female relatives. Materials and Methods: Female adolescents from a rural middle school received the educational program. The program would be considered feasible and acceptable if more than 75% reported being satisfied with its contents. Changes in knowledge in the students and their relatives were evaluated using baseline and 4 months follow‐up questionnaires. Results: One hundred twenty‐six students were enrolled. The program was considered acceptable by 96% of the participants. The students' knowledge regarding breast cancer increased significantly from baseline to 4 months follow‐up (63% to 82%). One hundred ninety‐four female relatives completed the initial knowledge questionnaires. The relatives' knowledge regarding breast cancer showed a significant increase from baseline to 4 months follow‐up (55% to 61%). Conclusion: Implementing breast cancer educational programs for adolescents in rural communities is feasible and acceptable. The program increased the adolescents' knowledge on breast cancer, and promoted the intergenerational transmission of that knowledge to their female relatives. Intergenerational transmission of knowledge represents a potential method for providing population‐based health awareness education globally. Abstract : Breast cancer mortality rates in low‐ and middle‐income countries are higher than in the developed world. Programs aimed at enhancing education and awareness of breast cancer are a critical strategy to overcoming barriers to timely diagnosis in these countries. This article reports a program designed to educate adolescents on breast cancer with the end goal of promoting intergenerational transmission of breast cancer‐related knowledge to their older female relatives.